The Effectiveness of Digital Educational Games in Increasing Elementary School Students’ Interest in Learning Mathematics - Juniarmi, Intan (PT. Anagata Sembagi Education, 2025)
This study aims to investigate the effectiveness of digital educational games in increasing elementary school students’ interest in learning mathematics. Using a quasi-experimental design, the research involved two groups of fourth-grade students: one experimental group that received instruction through digital games and one control group taught using conventional methods. Data were collected through observation, questionnaires, and pretest-posttest measurements of students’ learning interest. The results showed that students in the experimental group experienced a significant increase in motivation and engagement compared to the control group. Digital games provided interactive and visually stimulating experiences that helped simplify abstract mathematical concepts and made learning more enjoyable. Furthermore, the games fostered collaborative learning and improved classroom dynamics. The findings support the integration of game-based learning in elementary mathematics instruction as a powerful tool to enhance students’ affective involvement and enthusiasm for learning. The study suggests that educators should consider incorporating digital games to create more engaging and student-centered learning environments.